Frequency and risk factors of bronchopulmonary dysplasia in low-birth-weight infants in Saudi Arabia: a 5-year experience - Ramadan A. Mahmoud; Mahmoud Abdelrahman; Ahmed Gharib; Ahmed Elagami; Adli Abdelrahim; Khalid Alfaleh (Hygeia Press di Corridori Marinella, 2024)
Background: Due to improved survival of extremely low-birth-weight (ELBW) infants, the frequency of bronchopulmonary dysplasia (BPD) has remained unchanged or even increased.  Objective: To study the frequency as well as the perinatal and neonatal risk factors of moderate-to-severe BPD and its related mortality in low-birth-weight (LBW) infants in a single-center study over 5 years in the Kingdom of Saudi Arabia (KSA).  Methods: A total of 461 LBW infants' files with gestational age (GA) ≤ 32 weeks that met the inclusion criteria were retrospectively reviewed. Maternal and neonatal characteristics were evaluated. Furthermore, the hospital course of management of LBW infants and outcomes of mortality and morbidity were recorded.  Results: The overall mortality rate in LBW and ELBW infants was 19.52% and 38.62%, respectively. At 36 weeks' corrected GA, the total BPD frequency in LBW and ELBW infants was 9.87% and 32%, respectively. BPD(+) cases had a lower mean GA and birth weight than BPD(-) cases, 26 ± 2.68 weeks, 830 ± 340 grams and 29 ± 2.56 weeks, 1,395 ± 470 grams, respectively (p < 0.0001). The BPD(+) group had a significantly higher maternal chorioamnionitis infection rate, 8/39 (20.51%), than the BPD(-) group, 25/356 (7.02%) (p = 0.004), higher late-onset sepsis (11 [28.21%] and 54 [15.17%], p = 0.04). BPD(+) cases had a significantly higher risk of intubation in the delivery room, more frequently more than one dose of pulmonary surfactant, more invasive ventilation on day 1 and day 7, more days on oxygen therapy, more days on invasive and non-invasive ventilatory support, more days of hospitalization (115.41 ± 92.14 days compared to 43.72 ± 27.98 days in BPD[-]; all p < 0.0001).  Conclusion: ELBW infants had a 2-fold higher rate of mortality and a 3-fold higher rate of BPD, compared with LBW infants. The frequency of BPD increased with low GA/birth weight and BPD(+) cases had a higher risk for intubation in the delivery room, received more frequently more than one dose of pulmonary surfactant, remained for more days on either invasive or non-invasive ventilatory support, and had longer hospital stays.